1994
DOI: 10.1037/0021-843x.103.1.32
|View full text |Cite
|
Sign up to set email alerts
|

Personality and psychopathology: Genetic perspectives.

Abstract: Genetic factors exert an important influence on adult personality traits, accounting for anywhere between 30% and 60% of the variance. Heredity is also important for most forms of psychopathology and plays a major role in several theories that relate personality to psychopathology. Despite this, there has been surprisingly little multivariate genetic research reported on joint analyses of personality and psychopathology. The small amount of available data suggests that genes may account for over 50% of the obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
92
1
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(96 citation statements)
references
References 44 publications
2
92
1
1
Order By: Relevance
“…In many cases, especially when sample sizes are not particularly large, there may be insufficient power to detect an important genetic association between two traits in first degree relatives. 1\vin studies have added power for investigating the genetic covariation between traits because of the inclusion of MZ twins, who are genetically identical (Carey & DiLalla, 1994).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In many cases, especially when sample sizes are not particularly large, there may be insufficient power to detect an important genetic association between two traits in first degree relatives. 1\vin studies have added power for investigating the genetic covariation between traits because of the inclusion of MZ twins, who are genetically identical (Carey & DiLalla, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Of course, temporal ordering is a necessary but not sufficient condition for inferring that CD causes AD. Under certain restricted circumstances, for example, when one trait is largely influenced by genetic factors and the other is largely influenced by family environmental factors, structural equation models fitted to twin and family data can provide information about the direction of causation of the association between two traits (Carey & DiLalla, 1994;Duffy & Martin, 1994;Heath et al, 1993;Neale & Kendler, 1995). With data from the present study, these models were not able to resolve the direction of causation of the association between CD and AD.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the proportion of genetic covariation between AD and CD attributable to BU is (a X b)/(a X b + c X d). Similar models were used to estimate genetic correlations among AD, CD, and personality dimensions and to estimate the proportion of variation in AD or CD risk accounted for by other personality dimensions (see Carey & DiLalla, 1994;Neale & Cardon, 1992;or Slutske et aI., 1998, for more details about multivariate twin model fitting).…”
Section: Twin Model Fitting Of the Associations Of Ad And CD With Permentioning
confidence: 99%
“…aggressiveness, impulsivity, egocentrism and impersonal feelings and anti-social tendencies. 6 These are linked with the initiation and maintenance of drug use. 7 There is biological link between delusion and dependence.…”
Section: Discussionmentioning
confidence: 99%
“…4 Few studies have found a positive relationship between psychoticism and substance abuse. 5,2,3 High scorers on psychoticism exhibit some personality and behavioural traits such as impulsivity, aggressiveness, egocentrism and antisocial tendencies 6 and these traits have been shown to correlate with substance abuse. 7 Researchers have studied high levels of negative affect and an enduring desire for arousal and increased positive affect.…”
mentioning
confidence: 99%